Genetic modulator of stress resilience and blood pressure regulation: insights from polymorphic variation - Kumari, Bandana (International Journal of Research in Medical Sciences, 2025)
Neuropeptide Y (NPY) is a remarkably conserved neuropeptide distributed throughout the central and peripheral nervous systems, where it exerts broad influence over stress regulation and cardiovascular stability. While chronic stress typically contributes to increased blood pressure, a subset of individuals maintain normal levels despite similar stress exposure, suggesting the involvement of protective genetic factors within the NPY pathway. Variations in the NPY gene, particularly functional promoter polymorphisms such as rs16147 C>T and related haplotypes, appear to shape individual differences in stress responsiveness, sympathetic activation and emotional resilience. High-expression alleles are generally linked with reduced norepinephrine release, lower blood pressure and greater psychological stability under stress, whereas low-expression variants tend to enhance sympathetic tone and heighten vulnerability to anxiety and stress-related hypertension. Experimental studies reinforce the concept of NPY as a central sympathoinhibitory regulator, acting mainly through presynaptic Y₂ receptors within autonomic control centers. Recognizing these genetic influences offers valuable insight into why stress affects individuals so differently and opens new avenues for precision medicine. Genotypic profiling may ultimately aid in tailoring interventions for hypertension, anxiety and post-traumatic stress disorder. Moreover, pharmacological strategies targeting the NPY system such as Y₂ receptor agonists or agents that modulate epigenetic regulation, represents promising directions for future therapy. Continued longitudinal and translational research is essential to confirm causal mechanisms and to establish NPY as a clinically useful biomarker and therapeutic target in stress-related cardiovascular and neuropsychiatric disorders.